The implementation of traditional games in ntunhs taiwan sit-in students in indonesia - Fajar Awang Irawan; Dhias Fajar Widya Permana; Taufiq Hidayah; Wanda Kusuma Putri; Huang Wen Ching; Tania Arlita Safitri Prastiwi; Nonik Rahesti; Dina Syarafina Ghassani; Nur Suciati (Universitas Riau, 2023)
(English)This study aims to introduce the characteristics of the Indonesian nation in the form of traditional games as one of the efforts to preserve culture. Data is obtained from the process of observation, interviews, and documentation, which is then described by qualitative descriptive methods. The data analysis used in this study used the Miles and Huberman method. Participants in this study consisted of students of the National Taipei University of Nursing and Health Science who were visiting Semarang State University, as well as lecturers and students of Sports Science Semarang State University who were active in traditional games. The results obtained in this study show that traditional games have benefits for health and fitness. Traditional games are another facet of cultural heritage that needs to be conserved. One way to help preserve traditional games is to play them more often, engage with others, and promote them. This research is limited to the still-widely-ranging discussions about traditional games. The study is expected to consist of a short course focused on one of the original traditional games played in Indonesia.(Indonesian)Penelitian ini bertujuan untuk mengenalkan ciri khas bangsa Indonesia dalam bentuk permainan tradisional sebagai salah satu upaya pelestarian budaya. Data diperoleh dari proses observasi, wawancara, dan dokumentasi yang kemudian dijabarkan dengan metode deskriptif kualitatif. Analisis data yang digunakan pada penelitian ini menggunakan metode Miles dan Huberman. Partisipan pada penelitian ini terdiri dari mahasiswa National Taipei University of Nursing and Health Science yang sedang berkunjung ke Universitas Negeri Semarang serta dosen dan mahasiswa Ilmu Keolahragaan Universitas Negeri Semarang yang aktif dalam bidang permainan tradisional. Hasil yang didapat pada penelitian ini menunjukkan bahwa permainan tradisional memiliki manfaat untuk kesehatan dan kebugaran. Selain itu, permainan tradisonal menjadi salah satu warisan budaya yang perlu dilestarikan. Salah satu upaya untuk melestarikan permainan tradisional dapat melalui frekuensi dalam memainkan permainan tersebut, sosialisasi, dan melakukan publikasi terhadap permainan tradisional tersebut. Penelitian ini terbatas pada pembahasan terkait permainan tradisional yang masih cukup luas. Pada penelitian selanjutnya, diharapkan dapat melakukan short course yang berfokus pada salah satu permainan tradisional asli dari Indonesia.Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.